Case Report: Co-Existence of BRCA2 and PALB2 Germline Mutations in Familial Prostate Cancer With Solitary Lung Metastasis - Tang, Tang; Wang, Lin-ang; Wang, Peng; Tong, Dali; Liu, Gaolei; Zhang, Jun; Dai, Nan; Zhang, Yao; Yuan, Gang; Geary, Kyla; Zhang, Dianzheng; Liu, Qiuli; et al. (Frontiers in Oncology, 2020)
Background: Mutation-caused loss-of-function of factors involved in DNA damage response (DDR) is responsible for the development and progression of ~20% of prostate cancer (PCa). Some mutations can be used in cancer risk assessment and informed treatment decisions. Methods: Target capture-based deep sequencing of 11 genes was conducted with total DNA purified from the proband’s peripheral blood. Sanger sequencing was conducted to screen potential germline mutations in the proband’s family members. Targeted sequencing of a panel of 1021 genes was done with DNA purified from the tumor tissue. Results: Two previously unreported germline mutations in the DDR pathway, BRCA2 (c.8474_8487delCATACCCTATACAG, p.A2825Vfs*15) and PALB2 (c.472delC, p.Q158Rfs*19) were identified in a patient with metastatic prostate cancer. A specific therapeutic regimen including androgen deprivation therapy, locally radical radiotherapy, and systemic platinum chemotherapy worked well against his cancer. In addition, the metastatic ovarian cancer in the proband’s half-sister harboring the same BRCA2 germline mutation also responded well to platinum chemotherapy. Conclusions: The newly identified germline mutations in DDR plays important role in PCa development. Since specific regimen worked well against this cancer, screening of DDR mutation could provide better management for patients with these mutation-mediated PCa.